Development of a clinical predictive score for allergic reactions during oral food challenges in pediatric patients - Manatchanok Pattarakiatjaroen; Araya Yuenyongviwat; Pasuree Sangsupawanich (PLoS ONE, 2025)
Background The oral food challenge (OFC) is the gold standard for diagnosing food allergies; but, it carries risks ranging from mild to life-threatening reactions, including anaphylaxis. Understanding and predicting these reactions is critical for safe clinical practice. Objectives This study aimed to develop and validate a clinically predictive score for allergic reactions during OFCs in pediatric patients. Methods Using a retrospective database of pediatric patients undergoing OFCs at a pediatric outpatient clinic in Southern Thailand from January 2014 to December 2022, a multivariable predictive model was developed. Data on the reaction rates, demographics, and treatments were collected. Logistic regression analysis with predictor selection using a backward stepwise approach, was employed. The model’s performance was assessed using the area under the receiver operating characteristic curve (ROC), calibration, and classification measures. Results This study included 179 patients with an allergic reaction incidence of 12.3%. Predictors encompassed female, anaphylaxis and positive skin prick testing. The developed model achieved an ROC of 0.71. The patients were categorized into the low-risk (score 0–1) and high-risk (score 2–3) groups. Reaction rates during the OFCs were 6.7% in the low-risk group and 29.5% in the high-risk group. Conclusions Our scoring model demonstrated predictive ability for OFC reactions in pediatric patients, offering valuable insights for clinical risk assessment.